Highly efficient diode-pumped alkali-vapor amplification with near-extreme-limit gain - Kim, Heewoo; Jeong, Yujae; Hwang, Kyeongjun; Yeom, Dong Il; Moon, Han Seb (Optics Express, 2022)
We report high-efficiency optical amplification with near-extreme-limit gain from a diode-pumped Cs vapor cell. We used wavelength-division multiplexing to couple 852 nm pump and 895 nm seed lasers to achieve nearly overlapping spatial modes in the Cs vapor cell. We investigated the amplification factor as a function of the focal length of the lens focusing on the combined pump and seed signals and determined the optimal focal length under our experimental conditions. The small-signal amplification factor from the Cs vapor cell reached >30 dB at 240 mW pump power, and the optimal optical amplification factor per pump power was 4171/W.
Keywords: Alkali vapors; Amplification factors; Diode-pumped; Focal lengths; Higher efficiency; Optical amplifications; Pump power; Seed lasers; Spatial modes; Vapor cells